Enhancement of Insulin/PI3K/Akt Signaling Pathway and Modulation of Gut Microbiome by Probiotics Fermentation Technology, a Kefir Grain Product, in Sporadic Alzheimer’s Disease Model in Mice - El Sayed, Nesrine S.; Kandil, Esraa A.; Ghoneum, Mamdooh H. (Frontiers in Pharmacology, 2021)
Sporadic Alzheimer’s disease (AD) is the most common neurodegenerative disorder with cognitive dysfunction. Remarkably, alteration in the gut microbiome and resultant insulin resistance has been shown to be connected to metabolic syndrome, the crucial risk factor for AD, and also to be implicated in AD pathogenesis. Thus, this study, we assessed the efficiency of probiotics fermentation technology (PFT), a kefir product, in enhancing insulin signaling via modulation of gut microbiota to halt the development of AD. We also compared its effectiveness to that of pioglitazone, an insulin sensitizer that has been confirmed to substantially treat AD. AD was induced in mice by a single injection of intracerebroventricular streptozotocin (STZ; 3 mg/kg). PFT (100, 200, 400 mg/kg) and pioglitazone (30 mg/kg) were administered orally for 3 weeks. Behavioral tests were conducted to assess cognitive function, and hippocampal levels of acetylcholine and β-amyloid (Aβ1-42) protein were assessed along with histological examination. Moreover, the expression of the insulin receptor, phosphoinositide 3-kinase (PI3K), protein kinase B (Akt), insulin degrading enzyme (IDE), glycogen synthase kinase-3β (GSK-3β), mammalian target of rapamycin (mTOR), and phosphorylated tau were detected. Furthermore, oxidative stress and inflammatory biomarkers were estimated. Treatment with PFT reversed STZ-induced neurodegeneration and cognitive impairment, enhanced hippocampal Ach levels, and reduced Aβ1-42 levels after restoration of IDE activity. PFT also improved insulin signaling, as evidenced by upregulation of insulin receptor expression and activation of PI3K/Akt signaling with subsequent suppression of GSK-3β and mTOR signaling, which result in the downregulation of hyperphosphorylated tau. Moreover, PFT significantly diminished oxidative stress and inflammation induced by STZ. These potential effects were parallel to those produced by pioglitazone. Therefore, PFT targets multiple mechanisms incorporated in the pathogenesis of AD and hence might be a beneficial therapy for AD.